Aerodynamic design of a high-speed intake test rig for propulsion integration research - Migliorini, Matteo; Zachos, Pavlos K.; MacManus, David G.; Martin, Peter G. (American Institute of Aeronautics and Astronautics (AIAA), 2025)
Inlet flow distortion is a critical factor in supersonic air induction systems, primarily due to its complex spatial variations and significant temporal unsteadiness. These characteristics can have a substantial impact on the performance and reliability of propulsion systems. Conducting experiments at an early stage of technology readiness can help mitigate risks associated with industrial testing and certification processes. This paper is part of a broader programme aimed at advancing experimental capabilities for high-speed propulsion system integration. The research focuses on incorporating advanced, non-intrusive measurement techniques alongside current industry-standard methods to better characterize engine compatibility. The paper details the optimization process for designing a fixed-throat supersonic nozzle that delivers high-quality flow at Mach 1.8, the structural and functional design of the working section. The integration of an intake test article is described, together with instrumentation for measuring synchronous total pressure and swirl distortion at the aerodynamic interface plane of the intake. Preliminary computational work is also presented, evaluating the flow quality within the working section and investigating the distribution of bypass flow in the radial exhaust.